2022
DOI: 10.1093/europace/euac116
|View full text |Cite
|
Sign up to set email alerts
|

Personalized ablation vs. conventional ablation strategies to terminate atrial fibrillation and prevent recurrence

Abstract: Aims The long-term success rate of ablation therapy is still sub-optimal in patients with persistent atrial fibrillation (AF), mostly due to arrhythmia recurrence originating from arrhythmogenic sites outside the pulmonary veins. Computational modelling provides a framework to integrate and augment clinical data, potentially enabling the patient-specific identification of AF mechanisms and of the optimal ablation sites. We developed a technology to tailor ablations in anatomical and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
0
33
0
4
Order By: Relevance
“…used different combinations of imaging (LGE and CT) and mapping (EAM) data from 29 perAF patients to create patient-specific atrial models that were used to determine personalized ablation targets. 75 The results from this study showed that PVI had the lowest acute success rate and that personalized fibrosis-targeted ablation resulted in success rates as high as 90.9%, although it required EAM data for model construction. 75 Lastly, the results from these mechanistic models may also be used to prevent AF recurrence, where the features of a patient's LGE MRI scan and personalized simulations are used to predict the patient's risk of AF recurrence.…”
Section: Computational Models Of Af – Uniting Insights From Animal Mo...mentioning
confidence: 81%
“…used different combinations of imaging (LGE and CT) and mapping (EAM) data from 29 perAF patients to create patient-specific atrial models that were used to determine personalized ablation targets. 75 The results from this study showed that PVI had the lowest acute success rate and that personalized fibrosis-targeted ablation resulted in success rates as high as 90.9%, although it required EAM data for model construction. 75 Lastly, the results from these mechanistic models may also be used to prevent AF recurrence, where the features of a patient's LGE MRI scan and personalized simulations are used to predict the patient's risk of AF recurrence.…”
Section: Computational Models Of Af – Uniting Insights From Animal Mo...mentioning
confidence: 81%
“…Thus, interruption of autophagy flux by HCQ may prevent the electrical and structural remodeling of AF. Cardiac computational modeling approaches can be used to quantitatively understand complex subcellular or spatiotemporal dynamics of AF [23,25,33] and to perform personalized AF ablation as shown in the OPTIMA [22] and PersonAL [23] studies. Recently, these computational models have also been utilized for in-silico antiarrhythmic drug trials and drug toxicity screening [18,19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 11, 2022. ; https://doi.org/10.1101/2022.12.07.519115 doi: bioRxiv preprint models have been developed based on quantitative patch-clamp data of human cardiomyocytes [20,21] and recently utilized to perform computational modeling-guided ablation of atrial fibrillation (AF) [22,23] or in-silico antiarrhythmic drug trials [24,25]. However, most recent preclinical studies have focused on the HCQ-associated TdP risk stratification in ventricular cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used the Pacing at the End of the Effective Refractory Period (PEERP) protocol to localize emergent AF episodes, and then connected localized ablations to the closest non-conductive barrier to prevent recurrence of AF ( Azzolin et al, 2021b ). This study found that the proposed Personalized Ablation Lines (PersonAL) plan, consisting of iteratively targeting emergent high dominant frequency regions, outperformed state-of-the-art anatomical and substrate ablation strategies ( Azzolin et al, 2022b ).…”
Section: Applications Of Digital Twin Techniques In Atrial Fibrillati...mentioning
confidence: 99%